Optimalisasi Kompetensi Mahasiswa Ilmu Perpustakaan Melalui Learning Community - Sefri Doni (Maktabatuna, 2019)
The demand for qualifications for a job will continue to be higher, including in the field of a library while competence is too slow to be repaired. This certainly will cause alumni absorption on employment to be low and extra time is needed for alumni to adjust. This problem can be overcome by preparing prospective alumni early by optimizing the Competency of Library Science Students through the Learning Community. Optimization of Competencies in Library Science Students Through the Learning Community is a form of group assignments to learn and explore certain fields with a more flexible time. Starting from simple steps by gathering members, determining topics and doing joint learning while still empowering members by occasionally inviting other communities.